DNA Methylation Patterns Are Associated with n–3 Fatty Acid Intake in Yup'ik People. Issue 4 (29th January 2014) - Aslibekyan, Stella; Wiener, Howard W.; Havel, Peter J.; Stanhope, Kimber L.; O'Brien, Diane M.; Hopkins, Scarlett E.; Absher, Devin M.; Tiwari, Hemant K.; Boyer, Bert B.
Abstract: A large body of evidence links a high dietary intake of n–3 (ω-3) polyunsaturated fatty acids (PUFAs) with improved cardiometabolic outcomes. Recent studies suggested that the biologic processes underlying the observed associations may involve epigenetic changes, specifically DNA methylation. To evaluate changes in methylation associated with n–3 PUFA intake, we conducted an epigenome-wide methylation association study of long-chain n–3 PUFA intake and tested associations between the diabetes- and cardiovascular disease–related traits. We assessed DNA methylation at ∼470, 000 cytosine–phosphate–guanine (CpG) sites in a cross-sectional study of 185Yup'ik Alaska Native individuals representing the top and bottom deciles of PUFA intake. Linear regression models were used to test for the associations of interest, adjusting for age, sex, and community group. We identified 27 differentially methylated CpG sites at biologically relevant regions that reached epigenome-wide significance ( P < 1 × 10 −7 ). Specifically, regions on chromosomes 3 (helicase-like transcription factor), 10 (actin α 2 smooth muscle / Fas cell surface death receptor), and 16 (protease serine 36/C16 open reading frame 67) each harbored 2 significant correlates of n–3 PUFA intake. In conclusion, we present promising evidence of association between several biologically relevant epigenetic markers and long-term intake of marine-derived n–3 PUFAs.